Open research: motivation, theory, and practice - Neylon, Cameron (Henry Stewart Talks, 2012)
Research works by building on the work of others, The web as a new tool: what is it good for?, How does this relate to the needs of researchers?, The research record is not web enabled, Lab notebook as blog, Automated tools, Using specialised services: putting research outputs where they best belong, An example: Open Notebook Solubility, Record is the collection of links between research outputs, Tools to build these links and records, Information overload, Social filtering, The need for open approaches, Conclusions